Dampak Kekosongan Obat di RSUD Kabupaten Karawang di Hubungkan dengan Regulasi BPJS Kesehatan - Eka Prima Wahyuning Tyas; Yuniar Rahmatiar; Muhammad Abbas (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
The availability of medicines is an essential part of fulfilling patients' rights to safe, quality, and sustainable healthcare services, especially for National Health Insurance (JKN) or BPJS Kesehatan participants. However, in practice, drug shortages still occur, directly impacting patients. This study analyzes the impact of drug shortages at Karawang Regency Hospital on fulfilling the rights of BPJS Kesehatan patients and the role of local governments in addressing them. Using a normative juridical method supported by interviews and literature studies, the results show that drug shortages result in delayed therapy, worsening patient health conditions, and the incurring of additional costs because patients must purchase medicines independently. This condition contradicts the provisions of Presidential Regulation Number 82 of 2018 and Presidential Regulation Number 59 of 2024 and has the potential to violate the cooperation agreement between BPJS Kesehatan and hospitals. Therefore, strengthening the management of drug planning, procurement, and control by local governments is necessary to ensure the protection of patient rights and compliance with BPJS Kesehatan regulations.